Readdressing the trade effect of the Euro: Allowing for currency misalignment - Jan Hogrefe; Benjamin Jung; Wilhelm K. Kohler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
We know that euro-area member countries have absorbed asymmetric shocks in ways that are inconsistent with a common nominal anchor. Based on a reformulation of the gravity model that allows for such bilateral misalignment, we disentangle the conventional trade cost channel and trade effects deriving from 'implicit currency misalignment'. Econometric estimation reveals that the currency misalignment channel exerts a significant trade effect on bilateral exports. We retrieve country specific estimates of the euro effect on trade based on misalignment. This reveals asymmetric trade effects and heterogeneous outlooks across countries for the costs and benefits from adopting the euro.
Keywords: F12; F13; F15; 330; Euro; gravity model; exchange rates; purchasing power parity; trade imbalances; Euro; Außenhandelseffekt; Kaufkraftparität; Wechselkurs; Gravitationsmodell; Kosten-Nutzen-Analyse; Eurozone